Extended Near-Infrared Photoactivity of Bi6Fe1.9Co0.1Ti3O18 by Upconversion Nanoparticles - Wen Ge; Zhiang Li; Tong Chen; Min Liu; Yalin Lu (Nanomaterials, 2018)
Bi6Fe1.9Co0.1Ti3O18 (BFCTO)/NaGdF4:Yb3+, Er3+ (NGF) nanohybrids were successively synthesized by the hydrothermal process followed by anassembly method, and BFCTO-1.0/NGF nanosheets, BFCTO-1.5/NGF nanoplates and BFCTO-2.0/NGF truncated tetragonal bipyramids were obtained when 1.0, 1.5 and 2.0 M NaOH were adopted, respectively. Under the irradiation of 980 nm light, all the BFCTO samples exhibited no activity in degrading Rhodamine B (RhB). In contrast, with the loading of NGF upconversion nanoparticles, all the BFCTO/NGF samples exhibited extended near-infrared photoactivity, with BFCTO-1.5/NGF showing the best photocatalytic activity, which could be attributed to the effect of {001} and {117} crystal facets with the optimal ratio. In addition, the ferromagnetic properties of the BFCTO/NGF samples indicated their potential as novel, recyclable and efficient near-infrared (NIR) light-driven photocatalysts.